Groundwater trace element changes were probably induced by the ML3.3 earthquake in Chaoyang district, Beijing - Chen, Yuxuan; Liu, Jianbo (Frontiers in Earth Science, 2023)
Geochemical composition changes in groundwater related to earthquakes have been documented in previous studies, and most such studies focused on the changes in major ions, hydrogen, oxygen isotopes, and geochemical gases. Changes in trace elements were suggested to be more sensitive to small earthquakes than the commonly used chemical constituents such as major ions, yet they received less attention. Beijing is located in the Zhangjiakou-Bohai seismic belt and experiences frequent occurrences of small earthquakes. In this paper, we collected groundwater samples from a hot spring in Yanqing district of Beijing weekly from August 2021 to August 2022. Each water sample contained 41 trace chemical compositions. During the sampling, an earthquake with a magnitude of ML3.3 occurred in the Chaoyang district of Beijing on 3 February 2022, so these trace elements changes were systematically monitored before and after the earthquake: Li, Sc, Ti, and Pb elements had upward changes before the earthquake, while Cu, Nb, Th, Zn, Tl, and U elements had downward changes before the earthquake. Eu (rare earth elements) had upward changes after the earthquake. At the same time, the earthquake caused no significant changes in the groundwater level in the seismic monitoring well near the Songshan spring. Such responses indicate that trace elements are likely to be more sensitive to crustal strain than groundwater level. We considered that the earthquake-induced rock cracks before or after the earthquake caused enhancing water-rock interaction and led to the migration of trace elements between the water column and rocks, which is the mechanism to explain the trace elemental changes. This study probably provides a comprehensive assessment of the sensitivity of trace element constituents to the earthquake. Furthermore, we suggest that more long-term continuous monitoring and research of trace elements in Beijing and Zhangjiakou-Bohai Fault Zone should be considered to explore the response mechanism of groundwater geochemistry to earthquakes in the future.